T3SS-Independent Uptake of the Short-Trip Toxin-Related Recombinant NleC Effector of Enteropathogenic Escherichia coli Leads to NF-κB p65 Cleavage - Stolle, Anne-Sophie; Norkowski, Stefanie; Körner, Britta; Schmitz, Jürgen; Lüken, Lena; Frankenberg, Maj; Rüter, Christian; Schmidt, M. Alexander (Frontiers in Cellular and Infection Microbiology, 2017)
Effector proteins secreted by the type 3 secretion system (T3SS) of pathogenic bacteria have been shown to precisely modulate important signaling cascades of the host for the benefit of the pathogens. Among others, the non-LEE encoded T3SS effector protein NleC of enteropathogenic Escherichia coli (EPEC) is a Zn-dependent metalloproteinase and suppresses innate immune responses by directly targeting the NF-κB signaling pathway. Many pathogenic bacteria release potent bacterial toxins of the A-B type, which - in contrast to the direct cytoplasmic injection of T3SS effector proteins - are released first into the environment. In this study, we found that NleC displays characteristics of bacterial A-B toxins, when applied to eukaryotic cells as a recombinant protein. Although lacking a B subunit, that typically mediates the uptake of toxins, recombinant NleC (rNleC) induces endocytosis via lipid rafts and follows the endosomal-lysosomal pathway. The conformation of rNleC is altered by low pH to facilitate its escape from acidified endosomes. This is reminiscent of the homologous A-B toxin AIP56 of the fish pathogen Photobacterium damselae piscicida (Phdp). The recombinant protease NleC is functional inside eukaryotic cells and cleaves p65 of the NF-κB pathway. Here, we describe the endocytic uptake mechanism of rNleC, characterize its intracellular trafficking and demonstrate that its specific activity of cleaving p65 requires activation of host cells e.g. by IL1β. Further, we propose an evolutionary link between some T3SS effector proteins and bacterial toxins from apparently unrelated bacteria. In summary, these properties might suggest rNleC as an interesting candidate for future applications as a potential therapeutic against immune disorders.